A Pilot One Group Feasibility, Acceptability, and Initial Efficacy Trial of LISTEN for Loneliness in Lonely Stroke Survivors - Laurie A. Theeke PhD, RN, FNP-BC; Jennifer A. Mallow PhD, RN, FNP-BC; Elliott Theeke BA (SAGE Publishing, 2021)
Introduction Loneliness is a prevalent problem for adult stroke survivors, and a known contributor to hypertension, secondary stroke, functional decline, poorer quality of life, and mortality in older adults. LISTEN (Loneliness Intervention using Story Theory to Enhance Nursing-sensitive outcomes), a theoretically based behavioral health intervention designed to target loneliness, in a sample of lonely survivors of ischemic stroke. Objectives: To assess the feasibility and acceptability of LISTEN (Loneliness Intervention using Story Theory to Enhance Nursing-sensitive outcomes) in lonely stroke survivors and to evaluate the initial efficacy of LISTEN for loneliness, depressive symptoms, neurological quality of life, and blood pressure in a sample of lonely survivors of ischemic stroke. Methods: The study design was framed using the psychoneuroimmunology paradigm and employed a prospective non-randomized one group design. Six adult stroke survivors were recruited from a Neurology outpatient clinic. Once consented and enrolled, participants attended 5 sequential weekly group sessions of LISTEN. Evaluations, field notes, and video recordings of each session were used to assess feasibility and acceptability of LISTEN. Quantitative data was collected at enrollment and at 1, 6, and 12 weeks post last LISTEN session to assess initial efficacy on loneliness (revised UCLA loneliness scale), depressive symptoms (PHQ-9), neurological quality of life (NeuroQoL), and blood pressure. SPSS was used for descriptive and comparative data analysis to examine within subject changes. Results: LISTEN was feasible to deliver in the selected clinical setting and participants rated LISTEN as highly useful, organized, and clear with an overall rating as excellent for loneliness. Participants reported significant decline in loneliness and improved scores on three subscales of the NeuroQoL; executive function, positive affect and well-being, and satisfaction with social roles. Recruiting stroke survivors for the trial was time intensive for the study team. Conclusions: Larger randomized trials of LISTEN in stroke survivors are needed to build evidence for the longer term effectiveness of LISTEN on loneliness, depressive symptoms, and quality of life. Future study designs will include planning to diminish barriers to recruitment.